Culture, nature, materiality and immateriality: interrelations in cultural heritage policies (PerCursos, 2021)
The legal instruments destined to the recognition and protection of the Brazilian Cultural Heritage underwent changes throughout the process of development of public policies aimed at the theme. This article aims to present a brief chronological retrieval of these legal instruments, highlighting discussions involving the concepts of nature and culture, materiality and immateriality, in addition to instigating public managers and researchers to incorporate social and environmental conditions in discussions on this topic. Methodologically, the research took place through a bibliographic survey in publications of the area, such as books, legislations and technical documents. It is concluded that it is currently impossible to work with the theme of cultural heritage without considering in an interrelated way with the four key concepts addressed in this article. Along these lines, there was a theoretical-conceptual advance in the discussions on the subject, but it is still necessary that the governmental agencies in the area restructure from this scenario.
Keywords: heritage; culture; nature; materiality; immateriality